Helicobacter pylori: pathogenesis - P. Sabanas; L. Jonaitis (Microbiota in Health and Disease)
In this review, we analyze the research articles and findings related to the pathogenesis of Helicobacter pylori infection, which were published between April 2023 and March 2024. H. pylori is the most common infectious disease worldwide. The clinical consequences of H. pylori infection are closely linked with the expression of virulence factors produced by the bacterium. To improve diagnostic tools and optimize the treatment outcomes of H. pylori infection it is essential to understand its pathogenesis. The latest mechanisms of how H. pylori interact with host tissue and microbiome, induces and modulates its pathogenicity, and influences the development of malignant disease as well as extragastric pathologies are represented in our review article. Treatment success rates by the current guidelines-based regimens remain suboptimal due to the increasing antimicrobial resistance of H. pylori. The mechanisms of resistance are still in the scope of research. We also describe the studies related to the possible mechanisms of resistance of H. pylori to antibacterial drugs.